Pelaksanaan Field trip sebagai Upaya Program Parenting di PAUD - Nuruzahra Luthfillah; Tia Salmah Paujiah; Rosma Bella Hindayanti; Anisa Tahira; Tia Salmah Paujiah; Purwati; Heri Yusuf Muslihin Yusuf Muslihin (Pendidikan Guru PAUD, FKIP, Univ Muhammadiyah Tasikmalaya, 2023)
The purpose of this study was to find out what efforts were made by the school in improving the parenting program implemented in the Sahara Integrated PAUD. The method used is a qualitative approach, the steps that have been carried out are based on a qualitative approach, namely by using data collection. The first time it was carried out, namely collecting data using data collection techniques in the form of observation, then conducting interviews, and the last stage was literature study. in depth with two resource persons who are educators at the Sahara integrated PAUD. The next stage is conducting a literature study, after data collection is complete, then the writer performs data reduction according to the research objectives followed by a description of the research results. The last is to make the final conclusion of the research. The results of this study are that field trip activities aim to overcome parents' difficulties in attending parenting programs implemented by institutions. Field trips are also a form of education for children, where children will be invited to a certain place or object somewhere. This field trip was also carried out as an effort to develop learning for children and to present a parenting program in the form of socialization or sharing discussions with parents of students.